Optimalisasi Pemasaran dan Pembukuan Usaha Kuliner untuk Meningkatkan Kinerja Bisnis - I Gde Wedana Arjawa; I Made Pulawan; I Ketut Puja Wirya Sanjaya (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The ASBHAK Ayam Krispy and Geprek Culinary Business Group face challenges in digital marketing and business bookkeeping that affect business performance. This service program aims to increase the capacity of partners through digital marketing training and participatory business financial management. The methods used include workshops, practical mentoring, module preparation, evaluative discussions, and digital platform implementation. The results of the activity showed an increase in partner understanding from 30% to 80%, as well as an increase in average business turnover of 25% in three months. The innovation of this program lies in the integration of hands-on practice-based training with digital technology that is easily accessible to MSME actors. This program is recommended to be replicated in other micro enterprises and developed into a sustainable program through online learning media and post-training mentoring so that the impact is wider and more sustainable